Book review: McGovern, M. 2017: A Socialist Peace? Explaining the Absence of War in an African Country. (July 2018) - Cochrane, Logan
McGovern, M. 2017: A Socialist Peace? Explaining the Absence of War in an African Country . Chicago, IL: University of Chicago Press. 249 pp. 30.00 (Paperback). ISBN: 9780226453606.